Combined effects of toxic Karenia mikimotoi and hypoxia on the juvenile abalone Haliotis discus hannai - Zhang, Yue; Song, Xiuxian; Zhang, Peipei (Frontiers in Marine Science, 2023)
Eutrophication in aquaculture areas concurrently leads to a high incidence of dissolved oxygen deficiency and toxic algal blooms. The combined effects of hypoxia and typical toxic algae on cultured organisms should be given sufficient consideration. Abalone breeding in China has greatly suffered from hypoxia and toxic Karenia mikimotoi blooms for many years. In this study, the individual and combined effects of the toxic dinoflagellate, K. mikimotoi, and hypoxia on juvenile abalone were determined based on abalone survival and oxidative stress indicators in their gills, hepatopancreas and hemolymph. The results showed that at a density of 106 to 3×107 cells/L, K. mikimotoi alone had a negligible influence on the survival of juvenile abalone under sufficient dissolved oxygen (DO) conditions. The 24 h-half lethal concentration (LC50) of DO alone for juvenile abalone was 0.75 mg/L in seawater. When K. mikimotoi was added at a density of 3×106 cells/L, the 24 h-LC50 of DO for juvenile abalone significantly increased to 2.59 mg/L, indicating obvious synergistic effects. The individual effects of hypoxia or K. mikimotoi on the oxidative stress indicators were limited, and only the superoxide dismutase (SOD) activity in the abalone gills significantly decreased under K. mikimotoi stress. However, the combined stress of hypoxia and K. mikimotoi led to significant changes in the antioxidant indicators in all tested tissues. The SOD activity in gills and hepatopancreas decreased, while the SOD and catalase (CAT) activity and malondialdehyde (MDA) content in the hemolymph increased due to the combined stress of hypoxia and K. mikimotoi. These results illustrated that the synergistic effects of hypoxia and K. mikimotoi caused serious oxidative damage in abalone and that the hemolymph exhibited greater sensitivity than did the gills and hepatopancreas. Further investigation found that K. mikimotoi increased the oxygen consumption rate in abalone and that hypoxia enhanced the hemolytic toxicity of K. mikimotoi. These results revealed that hypoxia and typical toxic algae cause synergistic harm to cultured organisms, which is expected to provide a new understanding of the destructive mechanisms of typical toxic algal blooms in aquacultural areas.